Biological and economic characteristics of the allotetraploid with genomic formula DDAuAu from the cereal family - K. U. Kurkiev; I. G. Adonina; M. Kh. Gadjimagomedova; L. V. Shchukina; T. A. Pshenichnikova (Вавиловский журнал генетики и селекции)
The synthesis  of new  allopolyploid  cereal  genotypes is an important task aimed  at involving new  genetic resources in breeding programs. Diploid species of the genera Triticum and Aegilops – bread  wheat  relatives – are an important source of agronomically  valuable traits. A tetraploid synthetic  with genomic formula DDAuAu was obtained by N.A. Navruzbekov through crossing Aegilops tauschii Coss. and Triticum urartu Thum. ex Gandil. The purpose of this work was to study  the  chromosomal composition and  biological  and  commercially  important traits of the  tetraploid. Cytogenetic analysis using fluorescent in situ hybridization  showed the  presence of all chromosomes of the D genome in the chromosomal complement of the synthetic. By means  of stepwise  vernalization, the winter habit was established for the tetraploid synthetic with the optimum vernalization requirement of 45 days. Under greenhouse conditions, two groups of genotypes were found whose flowering dates differed by 6.5 days, which may indicate an allelism at the Vrn-3 locus. The coloring of various organs of the tetraploid plant, such as coleoptile,  stem, anthers,  and glumes  of the spike, was revealed. The coloration  of the aleurone layer of the grain may indicate that the donor species T. urartu is a carrier of the Ba gene that controls its blue color. A new morphotype of leaf pubescence was found. In terms of productivity, the tetraploid is comparable to bread wheat. Grains are characterized by a supersoft structure and high wet gluten  content, from 39–45 to 65 %, in the field and greenhouse conditions, respectively. Thus, the tetraploid can be used to create  new wheat  genotypes as a source  of untapped genetic diversity, as well as a new genetic model  for studying  the patterns of evolution  of polyploid plants.